Work placements - a survival guide for students - Fanthome, Christine (UK Red Globe Press, 2004)
This book is an essential guide for students contemplating or embarking upon work placements. Using comments from students, employers and tutors, it includes guidelines on how to find an appropriate placement; audit skills; construct a strong CV and application; prepare for an interview and derive maximum benefit from the work placement experience. The book identifies common problems facing students, together with remedial strategies, and offers suggestions for tackling written and oral assignments. Finally, it shows how to create and implement a successful job-search strategy.
Age Group: Adult
Keywords: (ETB-2007) Travel and Tourism Work Placement